2004
DOI: 10.1261/rna.5910104
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a promoter in the putative internal ribosome entry site of the Saccharomyces cerevisiae TIF4631 gene

Abstract: The 5-region of the TIF4631 gene of Saccharomyces cerevisiae (encoding the translation initiation factor eIF4G1) was reported earlier to harbor a very active internal ribosome entry site (IRES) allowing for internal initiation of translation of TIF4631 mRNA. Here, we report the presence of a promoter in the region −112 to −36 relative to the translation initiation codon of the TIF4631 gene. This promoter stimulates transcription from a start site at position −36 and generates an mRNA that is actively translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…Keywords: IRES; TIF4631; eIF4G; translation; mRNA Verge et al (2004), in the February issue of RNA, reported that contrary to our earlier publication (Zhou et al 2001), the 5Ј leader of the TIF4631 mRNA does not enhance translation initiation or contain an IRES. The authors assert that they have identified a promoter, located 36-112 nucleotides upstream of the translation initiation site, and concluded in their abstract, "The data show that the IRES activity reported earlier is due to this promoter".…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Keywords: IRES; TIF4631; eIF4G; translation; mRNA Verge et al (2004), in the February issue of RNA, reported that contrary to our earlier publication (Zhou et al 2001), the 5Ј leader of the TIF4631 mRNA does not enhance translation initiation or contain an IRES. The authors assert that they have identified a promoter, located 36-112 nucleotides upstream of the translation initiation site, and concluded in their abstract, "The data show that the IRES activity reported earlier is due to this promoter".…”
Section: Introductionmentioning
confidence: 81%
“…However, Verge and colleagues recently suggested that this sequence does not facilitate translation initiation, but inhibits translation in vitro and has promoter activity when tested in cells. We disagree with these conclusions and respond by showing that the data are most consistent with an internal initiation mechanism.Keywords: IRES; TIF4631; eIF4G; translation; mRNA Verge et al (2004), in the February issue of RNA, reported that contrary to our earlier publication (Zhou et al 2001), the 5Ј leader of the TIF4631 mRNA does not enhance translation initiation or contain an IRES. The authors assert that they have identified a promoter, located 36-112 nucleotides upstream of the translation initiation site, and concluded in their abstract, "The data show that the IRES activity reported earlier is due to this promoter".…”
mentioning
confidence: 81%
See 3 more Smart Citations